Population aging and inequality: Evidence from the People's Republic of China - Xudong Chen; Bihong Huang; Shaoshuai Li (Asian Development Bank Institute (ADBI), 2017)
Population aging has significant economic and social costs, and this paper studies its impacts on inequality, both theoretically and empirically. First, we build a two-period overlapping-generation model with an uncertain lifetime and find that population aging has the overall effect of increasing income and consumption inequality within the society. For the empirical analysis, we use household data from the China Health and Nutrition Survey to assess the age effect on income and consumption inequality in the People's Republic of China and confirm the results predicted by the theoretical model.
Keywords: J11; J14; 330; population aging; income inequality; consumption inequality; overlapping-generation model